let f, g be Function of I,(); :: thesis: for a, b, c, d being Real
for O, I being Point of I st O = 0 & I = 1 & f is continuous & f is one-to-one & g is continuous & g is one-to-one & (f . O) `1 = a & (f . I) `1 = b & (g . O) `2 = c & (g . I) `2 = d & ( for r being Point of I holds
( a <= (f . r) `1 & (f . r) `1 <= b & a <= (g . r) `1 & (g . r) `1 <= b & c <= (f . r) `2 & (f . r) `2 <= d & c <= (g . r) `2 & (g . r) `2 <= d ) ) holds
rng f meets rng g

let a, b, c, d be Real; :: thesis: for O, I being Point of I st O = 0 & I = 1 & f is continuous & f is one-to-one & g is continuous & g is one-to-one & (f . O) `1 = a & (f . I) `1 = b & (g . O) `2 = c & (g . I) `2 = d & ( for r being Point of I holds
( a <= (f . r) `1 & (f . r) `1 <= b & a <= (g . r) `1 & (g . r) `1 <= b & c <= (f . r) `2 & (f . r) `2 <= d & c <= (g . r) `2 & (g . r) `2 <= d ) ) holds
rng f meets rng g

let O, I be Point of I; :: thesis: ( O = 0 & I = 1 & f is continuous & f is one-to-one & g is continuous & g is one-to-one & (f . O) `1 = a & (f . I) `1 = b & (g . O) `2 = c & (g . I) `2 = d & ( for r being Point of I holds
( a <= (f . r) `1 & (f . r) `1 <= b & a <= (g . r) `1 & (g . r) `1 <= b & c <= (f . r) `2 & (f . r) `2 <= d & c <= (g . r) `2 & (g . r) `2 <= d ) ) implies rng f meets rng g )

assume that
A1: ( O = 0 & I = 1 ) and
A2: ( f is continuous & f is one-to-one ) and
A3: ( g is continuous & g is one-to-one ) and
A4: (f . O) `1 = a and
A5: (f . I) `1 = b and
A6: (g . O) `2 = c and
A7: (g . I) `2 = d and
A8: for r being Point of I holds
( a <= (f . r) `1 & (f . r) `1 <= b & a <= (g . r) `1 & (g . r) `1 <= b & c <= (f . r) `2 & (f . r) `2 <= d & c <= (g . r) `2 & (g . r) `2 <= d ) ; :: thesis:
reconsider P = rng f as non empty Subset of () ;
A9: I is compact by ;
then consider f1 being Function of I,(() | P) such that
A10: f = f1 and
A11: f1 is being_homeomorphism by ;
reconsider Q = rng g as non empty Subset of () ;
consider g1 being Function of I,(() | Q) such that
A12: g = g1 and
A13: g1 is being_homeomorphism by A3, A9, Th45;
reconsider q2 = g1 . I as Point of () by ;
reconsider q1 = g1 . O as Point of () by ;
A14: Q is_an_arc_of q1,q2 by ;
reconsider p2 = f1 . I as Point of () by ;
reconsider p1 = f1 . O as Point of () by ;
A15: for p being Point of () st p in P holds
( p1 `1 <= p `1 & p `1 <= p2 `1 )
proof
let p be Point of (); :: thesis: ( p in P implies ( p1 `1 <= p `1 & p `1 <= p2 `1 ) )
assume p in P ; :: thesis: ( p1 `1 <= p `1 & p `1 <= p2 `1 )
then ex x being object st
( x in dom f1 & p = f1 . x ) by ;
hence ( p1 `1 <= p `1 & p `1 <= p2 `1 ) by A4, A5, A8, A10; :: thesis: verum
end;
A16: for p being Point of () st p in Q holds
( p1 `1 <= p `1 & p `1 <= p2 `1 )
proof
let p be Point of (); :: thesis: ( p in Q implies ( p1 `1 <= p `1 & p `1 <= p2 `1 ) )
assume p in Q ; :: thesis: ( p1 `1 <= p `1 & p `1 <= p2 `1 )
then ex x being object st
( x in dom g1 & p = g1 . x ) by ;
hence ( p1 `1 <= p `1 & p `1 <= p2 `1 ) by A4, A5, A8, A10, A12; :: thesis: verum
end;
A17: for p being Point of () st p in Q holds
( q1 `2 <= p `2 & p `2 <= q2 `2 )
proof
let p be Point of (); :: thesis: ( p in Q implies ( q1 `2 <= p `2 & p `2 <= q2 `2 ) )
assume p in Q ; :: thesis: ( q1 `2 <= p `2 & p `2 <= q2 `2 )
then ex x being object st
( x in dom g1 & p = g1 . x ) by ;
hence ( q1 `2 <= p `2 & p `2 <= q2 `2 ) by A6, A7, A8, A12; :: thesis: verum
end;
A18: for p being Point of () st p in P holds
( q1 `2 <= p `2 & p `2 <= q2 `2 )
proof
let p be Point of (); :: thesis: ( p in P implies ( q1 `2 <= p `2 & p `2 <= q2 `2 ) )
assume p in P ; :: thesis: ( q1 `2 <= p `2 & p `2 <= q2 `2 )
then ex x being object st
( x in dom f1 & p = f1 . x ) by ;
hence ( q1 `2 <= p `2 & p `2 <= q2 `2 ) by A6, A7, A8, A10, A12; :: thesis: verum
end;
P is_an_arc_of p1,p2 by ;
hence rng f meets rng g by A14, A15, A16, A18, A17, Th43; :: thesis: verum